2022
DOI: 10.1088/1361-648x/ac4dbf
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast carrier dynamics in a monolayer MoS2 at carrier densities well above Mott density

Abstract: Due to the growing interest in monolayer Molybdenum Disulfide (MoS2) in several optoelectronic applications like lasers, detectors, sensors, it is important to understand the ultrafast behavior of the excited carriers in this material. In this article, a comprehensive study of the charge carrier dynamics of a monolayer MoS2 flake has been studied using transient transmission technique near A-exciton under high excitation densities well above the Mott density. Fluence dependent studies has been carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…There are also interesting observations on 1L MoS 2 on the effect of the time-dependent electronic temperature on the emission 42,43 and fluence. 43–47 For example, femtosecond pump–probe spectroscopy found that electron–phonon scattering is responsible for an ultrafast redshift of the exciton resonance energy observed after photoexcitation.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…There are also interesting observations on 1L MoS 2 on the effect of the time-dependent electronic temperature on the emission 42,43 and fluence. 43–47 For example, femtosecond pump–probe spectroscopy found that electron–phonon scattering is responsible for an ultrafast redshift of the exciton resonance energy observed after photoexcitation.…”
Section: Introductionmentioning
confidence: 93%
“…There are also interesting observations on 1L MoS 2 on the effect of the time-dependent electronic temperature on the emission 42,43 and fluence. 43–47 For example, femtosecond pump–probe spectroscopy found that electron–phonon scattering is responsible for an ultrafast redshift of the exciton resonance energy observed after photoexcitation. 42 The energy from the cooling of hot carriers and from the formation of bound states is transferred to the phonon subsystem within 2 ps, though some sub-ps emission dynamics was also observed.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The mechanism of above dynamics processes is possible to be observed through the analysis of in situ high-pressure dynamics spectra. Therefore, it is possible to use high-pressure dynamic spectra to analyze the high-pressure affected mechanism of physical and chemical properties of various materials [68][69][70][71].…”
Section: Ultrafast Dynamics In Extreme Conditionsmentioning
confidence: 99%